ERP SYSTEMS ANALYSIS AND DESCRIPTION OF SYSTEMS - Ludboržs, Rihards; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
In this article, I will briefly describe what business management systems are and what is that different from the others systems. Today, this system is called the “Enterprise Resource Planning Systems”. The purpose of this article is to look into the substance of the ERP systems and to identify the benefits of using the ERP systems.